Variations of soil quality from continuously planting greenhouses in North China - Li, Jing; Xu, Yan; Liu, Hongguang (International Journal of Agricultural and Biological Engineering, 2019)
Vegetable greenhouses form a significant land utilisation pattern in China. A case study of the greenhouse soil quality changes and potential risk to humans under a specific long-term environment, which includes high fertilization rates, high temperatures and humidity levels and out-of-season cultivation, is presented in this study. Soil profiles of 72 representative solar greenhouses with various planting years were sampled in Shouguang City, which is the birthplace of winter greenhouse in China. The temporal distribution of soil quality changes were quantitatively evaluated through the application of a correlation analysis and soil quality assessment. The soil was highly enriched with phosphorus and potassium and had low organic matter content. The organic matter, nitrogen, phosphorus and potassium contents increased with the years planted, reached their peak values after 5-10 a, and declined as the soil layer’s depth increased. The infiltration rate of nitrate was relatively high, which poses risks to underground water safety. A comprehensive soil quality assessment revealed that in vegetable greenhouses planted for different periods, the soil quality improved at first and then sharply declined after 10 a. Studying greenhouse soil quality changes will aid in implementing nutrient management strategies to improve the soil quality and sustainable development programs for the vegetable industry. Keywords: vegetable greenhouse, facility agriculture, planting years, soil quality, microbial activity DOI: 10.25165/j.ijabe.20191201.4092 Citation: Li J, Xu Y, Liu H G. Variations of soil quality from continuously planting greenhouses in North China. Int J Agric & Biol Eng, 2019; 12(1): 139–145.